Zika virus: A possible emerging threat for Bangladesh! - Hossain, Md Golzar; Nazir, KHM Nazmul Hussain; Saha, Sukumar; Rahman, Md Tanvir (Journal of Advanced Veterinary and Animal Research, 2019)
Zika virus, a member of Flaviviridae is the etiology of Zika or Zika fever or Zika virus (ZIKV) disease characterized by mild symptoms similar to very mild form of Dengue or Chikungunya. The virus transmits through Aedes mosquitoes, particularly by Aedes aegypti. The most dangerous effect of ZIKV infection is the ability of the virus to cause microcephaly and congenital malformation to the newborn baby if the mother is infected. The neurological disorders including Guillain-Barré syndrome might be associated with adults and children due to ZIKV infections. Zika has emerged as a serious global public health problem as it has been found in 87 countries, particularly in Africa, America, and Asia and has no vaccine and treatment so far. Bangladesh is at a high risk of ZIKV infection and we consider ZIKV as a possible emerging threat for Bangladesh. This short review summarizes the insights of ZIKV infection, present status of the disease in Bangladesh and its neighboring countries, and recommendations for necessary preparations and strategies to be taken for effective controlling of the ZIKV infection in Bangladesh before getting any havoc. J. Adv. Vet. Anim. Res., 6(4): 575-582, December 2019